2010
DOI: 10.1530/eje-09-1010
|View full text |Cite
|
Sign up to set email alerts
|

Therapies for the medical management of persistent hypoglycaemia in two cases of inoperable malignant insulinoma

Abstract: Objective: Hypoglycaemia poses a significant management challenge in patients with unresectable functional malignant insulinoma. Novel agents such as mammalian target of rapamycin (mTOR) inhibitors and radiolabelled peptides may be effective where there is failure of conventional therapy. Design: We present the cases of two men diagnosed with inoperable malignant insulinoma and hepatic metastases who developed severe symptomatic hypoglycaemia, and review potential therapies for glycaemic support. Method: Despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 29 publications
(41 reference statements)
2
48
0
3
Order By: Relevance
“…Data on everolimus in the control of hypoglycemic symptoms have been recently published (20,21,22,23). Our study confirms these data, with the largest number of patients ever reported in the literature and a significant duration of follow-up.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Data on everolimus in the control of hypoglycemic symptoms have been recently published (20,21,22,23). Our study confirms these data, with the largest number of patients ever reported in the literature and a significant duration of follow-up.…”
Section: Discussionsupporting
confidence: 88%
“…In two of four patients, partial responses were observed at 16 and 29 months. Four other case reports mentioned successful efficacy of mTOR inhibitors in controlling hypoglycemia (11,21,22,23), although failure to control hypoglycemic symptoms was reported in one case (24).…”
Section: Introductionmentioning
confidence: 99%
“…Hipoglisemi kontrolünde Diazoksid, beta blokerler, difenilhidantoin, somatostatin analogları ve everolimus kullanılabilmektedir (13,14,15). Diazoksid ATP duyarlı potasyum kanallarını açarak insü-linoma hücrelerinden insülin salınımını inhibe eder.…”
Section: Resim 1: Pankreas Başında Kitleunclassified
“…In addition, even when total removal of the tumour has been performed with a R0-resection, recurrence is frequent (about 60% after a follow-up of 3 years) and the recurrence-free median survival is 5 years (Danforth et al 1984). Treatments other than surgery combine local or regional treatments such as intra-arterial chemotherapy or chemoembolization of liver metastases (Roche et al 2003) and radiofrequency (Berber et al 2002), and systemic treatments such as radionuclide systemic administration (Ong et al 2010), cytotoxic chemotherapy (traditional combination of streptozotocin, doxorubicin and 5-fluoro-uracil and more recently, capecitabine and temozolomide) (Moertel et al 1992;Strosberg et al 2008;Strosberg et al 2011), or targeted therapies (Kulke et al 2006;Dimou et al 2010) (Raymond et al 2011;Yao et al 2011). Symptomatic treatment of insulinomas aims at achieving short-term control of the hypoglycaemia while awaiting the effects of anti-tumour treatment or when anti-tumour treatments do not prove to be effective.…”
Section: Malignant Insulinomasmentioning
confidence: 99%
“…One should choose as first-line therapies medications that can achieve short-term control of hypoglycaemic spells, and do not jeopardize (by their possible adverse effects) the following use of other treatments. A few recent studies have addressed the issue of the control of severe hypoglycaemic spells in patients with inoperable malignant insulinomas (Bourcier et al 2009;Ong et al 2010;Maiza et al 2011). All the medications used to treat hypoglycaemia in benign insulinomas can be employed, but in most cases, a combination of several hyperglycaemic medications is necessary (Vezzosi et al 2008).…”
Section: Malignant Insulinomasmentioning
confidence: 99%